Endogenous α‐calcitonin‐gene‐related peptide promotes exercise‐induced, physiological heart hypertrophy in mice. (13th March 2014) - Schuler, B.; Rieger, G.; Gubser, M.; Arras, M.; Gianella, M.; Vogel, O.; Jirkof, P.; Cesarovic, N.; Klohs, J.; Jakob, P.; Brock, M.; Gorr, T. A.; et al.
Abstract Aim It is unknown how the heart distinguishes various overloads, such as exercise or hypertension, causing either physiological or pathological hypertrophy. We hypothesize that alpha‐calcitonin‐gene‐related peptide (αCGRP), known to be released from contracting skeletal muscles, is key at this remodelling. Methods The hypertrophic effect of αCGRP was measured in vitro (cultured cardiac myocytes) and in vivo (magnetic resonance imaging) in mice. Exercise performance was assessed by determination of maximum oxygen consumption and time to exhaustion. Cardiac phenotype was defined by transcriptional analysis, cardiac histology and morphometry. Finally, we measured spontaneous activity, body fat content, blood volume, haemoglobin mass and skeletal muscle capillarization and fibre composition. Results While αCGRP exposure yielded larger cultured cardiac myocytes, exercise‐induced heart hypertrophy was completely abrogated by treatment with the peptide antagonist CGRP(8‐37). Exercise performance was attenuated in αCGRP−/− mice or CGRP(8‐37) treated wild‐type mice but improved in animals with higher density of cardiac CGRP receptors (CLR‐tg). Spontaneous activity, body fat content, blood volume, haemoglobin mass, muscle capillarization and fibre composition were unaffected, whereas heart index and ventricular myocyte volume were reduced in αCGRP−/− mice and elevated in CLR‐tg. Transcriptional changes seen in αCGRP−/− (but not CLR‐tg) hearts resembled maladaptive cardiac phenotype. Conclusions Alpha‐calcitonin‐gene‐related peptide released by skeletal muscles during exercise is a hitherto unrecognized effector directing the strained heart into physiological instead of pathological adaptation. Thus, αCGRP agonists might be beneficial in heart failure patients.